Letter Writing and Critical Self-Reflection: An Insiders Account of Academic Casualisation in the Australian Neoliberal University. Issue 3 (November 2022) - Murphy, Jennifer Joy; Down, Barry; Price, Anne Elizabeth
Sharing the lived experience of academic casualisation is challenging, based on a power imbalance with many oppositional points, including cost savings versus fair wages, precarity versus security. As researcher/participant, Jennifer initially struggled with sharing experiences emotionally and academically without stripping humanity and affect from her writing. Drawing on the tradition of critical autoethnography, this article uses letter writing as a means of investigating personal-professional experience through critical self-reflection. These letters are written to a fictional colleague (Q) for the purpose of 'wondering aloud' about her experience of casualised labour and the difficulties of constructing a personal-professional identity within the context of the Australian neoliberal university.